Bottom-Up Attention Orienting in Young Children with Autism. - Amso, Dima; Haas, Sara; Tenenbaum, Elena; Markant, Julie; Sheinkopf, Stephen (Journal of Autism & Developmental Disorders, 2014)
We examined the impact of simultaneous bottom-up visual influences and meaningful social stimuli on attention orienting in young children with autism spectrum disorders (ASDs). Relative to typically-developing age and sex matched participants, children with ASDs were more influenced by bottom-up visual scene information regardless of whether social stimuli and bottom-up scene properties were congruent or competing. This initial reliance on bottom-up strategies correlated with severity of social impairment as well as receptive language impairments. These data provide support for the idea that there is enhanced reliance on bottom-up attention strategies in ASDs, and that this may have a negative impact on social and language development.